The holist tradition in twentieth century genetics. Wilhelm Johannsen's genotype concept - Roll-Hansen, Nils (Blackwell Science Inc, 2014)
The terms ‘genotype’, ‘phenotype’ and ‘gene’ originally had a different meaning from that in the Modern Synthesis. These terms were coined in the first decade of the twentieth century by the Danish plant physiologist Wilhelm Johannsen. His bean selection experiment and his theoretical analysis of the difference between genotype and phenotype were important inputs to the formation of genetics as a well-defined special discipline. This paper shows how Johannsen's holistic genotype theory provided a platform for criticism of narrowly genocentric versions of the chromosome theory of heredity that came to dominate genetics in the middle decades of the twentieth century. Johannsen came to recognize the epoch-making importance of the work done by the Drosophila group, but he continued to insist on the incompleteness of the chromosome theory. Genes of the kind that they mapped on the chromosomes could only give a partial explanation of biological heredity and evolution.